A quantum chemical study on the formation of phosphorus mononitride - Viana, Rommel B.; Pereira, Priscila S. S.; Macedo, Luiz G. M. [UNESP]; Pimentel, Andre S. (Elsevier B.V., 2009)
The chemical mechanism of the (1)PN formation was successfully studied by using the CCSD(T)/6-311++G(3df,3pd) level of theory. The (1)NH(3) + (3)PH and (4)P + NH(3) reaction paths are not energetically favorable to form the (1)PN molecule. However, the (3)NH + (3)PH, (4)N + (3)PH(3), (4)N + (3)PH, (4)P + (3)NH, and (4)P + (2)NH(2) reaction paths to form the (1)PN molecule are only energetically favorable by taking place through specific transition states to form the (1)PN molecule. The NH(3) + (3)PH, (4)N + (1)PH(3), NH(3) + (4)P, and (4)N + (2)PH(2) reactions are spin-forbidden and the probability of hopping for these reactions was estimated to be 0 by the Landau-Zener theory. This is the first detailed study on the chemical mechanism for the (1)PN formation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Planetary chemistry; Nitrogen chemistry; Quantum chemical calculations; Phosphorus chemistry; Potential energy surface; Spin-forbidden reactions